Thoracal Thoracic Spinal Anesthesia In Mammae Tumors Excision Surgery - Yulis, Rina Yuliana; Tanra, Andi Husni; Harahap, Wirawan (Fakultas Ilmu Kesehatan, 2025)
Thoracic spinal anesthesia (TSA) is a regional anesthetic technique where the local anesthetic is injected into the thoracic subarachnoid space. It provides rapid onset of sensory and motor block, with segmental anesthesia suitable for surgeries in the thoracic and upper abdominal regions. Compared to general anesthesia (GA), TSA offers various advantages, including hemodynamic stability, decreased stress response, and superior postoperative pain control. We present a case of a 46-year-old female undergoing excision of a left breast tumor under thoracic spinal anesthesia at the T6–T7 level. The procedure was completed successfully without complications, and the patient reported satisfactory intraoperative and postoperative experiences. TSA can be a safe and effective alternative to GA in selected breast surgery cases, with potential benefits including reduced opioid use, stable intraoperative hemodynamics, and faster recovery.